A new room-temperature multiferroic material: Y2FeAlO6. Issue 8 (15th April 2021) - Song, Baofu; Shen, Jingdong; Zhao, Huihui; Kumar, Ashwini; Xu, Qingyu; Zhai, Ya; Li, Qi
Abstract: In this paper, we report the finding and basic characterization of a new multiferroic material in the form of the Y2 FeAlO6 (YFAO) double perovskite with orthorhombic structure. In order to study the structural and multiferroic properties in detail, we prepared the polycrystalline YFeO3 (YFO) and Y2 FeAlO6 ceramic samples through traditional high temperature solid-state reaction method. XRD analysis confirmed that these two samples are single-phase and all the peaks in the pattern can be indexed with orthorhombic symmetry of the Pnma space group. Compared to YFO, YFAO is more symmetric, and has a more stable crystalline structure and smaller grain size. The Fe ion in YFO and YFAO are in the mixed oxidation state of Fe 2+ and Fe 3+, while the relative amount of Fe 2+ in YFAO is higher than that of YFO. Al 3+ with filled 2p orbital and grain refinement may be the main reasons for the greatly enhanced multiferroicity of YFAO. The magnetic properties of YFO and YFAO are mainly dominant antiferromagnetism and weak ferromagnetism, and the exchange bias effect disappears in YFAO. The coexistence of ferroelectricity and ferromagnetic orders at room temperature in YFAO promises new opportunities and improvements in next generation applications for spintronic, information storage, and sensors etc.